A Comparative Analysis of Different Carbon Cap Policies on the Economic Lot-Sizing Problem with Remanufacturing - Quezada-Valenzuela, F; Davila-Galvez, S; Vallecilla-Galeano, A (Taylor and Francis Ltd., 2025)
This paper investigates the implementation of carbon cap policies within a remanufacturing production system, focussing on a single-item lot-sizing problem aimed at meeting the demand for end-of-life products under four distinct carbon cap policies. Our study, motivated by the operational dynamics of ECOCITEX, a Chilean textile remanufacturing company, explores the balance between operational costs, carbon emissions, and production levels in response to environmental policies. We introduce a mixed-integer linear programming (MILP) formulation to address economic lot-sizing with considerations for both remanufacturing and carbon emissions constraints. Through extensive computational experiments, we assess the impact of various carbon emissions policies on production and emissions levels and their associated costs, finding that global and rolling-horizon policies offer the best trade-off between emission reductions and production cost increases. This leads to more environmentally friendly production policies for remanufactured products without compromising financial sustainability. The findings underscore the importance of flexibility in environmental policies for remanufacturing operations, suggesting that stringent carbon caps, while beneficial for emission reductions, may pose challenges to demand fulfillment and cost management. For managers, this highlights the critical need for adaptive policy frameworks that support sustainable production objectives without impeding operational efficiency. © 2025 Informa UK Limited, trading as Taylor & Francis Group.